LANGUAGE CHOICE IN MULTILINGUAL CONTEXT: THE USE OF L1 IN THE HOSPITALITY ENGLISH COURSES - Ni Putu Era Marsakawati (Universitas Islam Sultan Agung, 2017)
The present study presents the perception of lecturers on the use of the first language in the foreign language classroom, particularly in a tourism vocational institution in a multilingual context. The participants were 2 lecturers teaching Hospitality English: one lecturer was teaching English for Front Office and one lecturer was teaching English for Food and Beverage. The data were collected through administering questionnaire and interview. The obtained data were analyzed qualitatively. The results show that lecturers perceived the use of the first language as positive and part of learning process. They used the first language mainly as a pedagogical device for clarification, for establishing rapport, saving time, and discipline. The findings might have significant implications for EFL language teachers regarding the facilitative effects of L1 use in the foreign language classrooms. The EFL teachers need to consider the EFL classroom context as a multilingual social space in which teachers and students take advantage of dynamic, creative and pedagogically effective use of both the target language and the learners. Keywords: first language use, lecturers ‘perspective, multilingual context